ICTV Virus Taxonomy Profile: Closteroviridae - Fuchs, Marc (Microbiology Society, 2020)

(untitled) (J Gen Virol)
Viruses in the family Closteroviridae have a mono-, bi- or tripartite positive-sense RNA genome of 13–19 kb, and non-enveloped, filamentous particles 650–2200 nm long and 12 nm in diameter. They infect plants, mainly dicots, many of which are fruit crops. This is a summary of the ICTV Report on the family Closteroviridae, which is available at ictv.global/report/closteroviridae.